Problems of assessing the severity of the state of elderly patients with community-acquired pneumonia caused by Klebsiella pneumoniae - V. I. Sakharov; P. I. Mironov; I. A. Ruslyakova; V. A. Rudnov (Вестник анестезиологии и реаниматологии)
It is known that the greatest difficulties in predicting the outcome of severe community-acquired pneumonia occur in elderly patients with gram-negative pneumonia.The objective: to compare the differentiating capacity of the PSI/PORT, SOFA, APACHE II, and MODS-2 scales in elderly patients with severe community-acquired pneumonia caused by K. pneumonia.Subjects: The study has been designed as retrospective, multicenter, controlled, and non-randomized. Inclusion criteria: clinical and laboratory, x-ray diagnosis of community-acquired pneumonia associated with Klebsiella pneumoniae with SOFA scores as 2 and more points. The severity of the patient's condition and prognosis were assessed using the SOFA, MODS-2, and PSI/ PORT scales when the patient was admitted to the ICU, further changes in the state were assessed after 72 hours of intensive care and by the outcome. The time spent in the ICU, the frequency of detection of bacteremia, and the need for renal replacement therapy (RRT) were evaluated. The following parameters were analyzed: co-morbodities, structure of multiple organ failure, validity of the information value of SOFA, APACHE II, and MODS-2 scales.Results. The age of the patient over 70 years increased the risk of death by 1.2 times (OR = 1.21). There were no significant differences in the frequency of individual nosologies of comorbidity. The development of multiple organ failure syndrome increased the possibility of patient death by more than three times (OR = 3.4). The probability of death of the patient when acute renal damage developed in the structure of multi-organ pathology was even more significant (OR = 8.5). Only the АРАСНЕ II (AUC ROC 0.677 ± 0.053) and SOFA (AUC ROC 0.708 ± 0.052) scales demonstrated moderate informational value in predicting the risk of death in the studied patients.Conclusion: When assessing the prognosis of the outcome in elderly patients with severe community-acquired pneumonia caused by Klebsiella pneumoniae, it is advisable to use the SOFA and APACHE II scales.